The molecular basis for host responses to Marek's disease viruses integrated with different retro-viral long terminal repeat. (16th June 2018) - Zhou, Zhongwen; Cui, Ning; Su, Shuai; Sun, Shuhong; Cui, Zhizhong
ABSTRACT: Integration of retro-viral long terminal repeat ( LTR ) into the Marek's disease virus (MDV ) genome can occur both in co-cultivation cell cultures and naturally in dual infected chickens. It is clear that the LTR insert is associated with the pathogenicity of MDV. The objective of this study was to compare the host responses to MDV with a different retro-viral LTR insert. Gene-chip containing chicken genome was employed to investigate the gene transcription profile of chicken embryo fibroblasts cells, and 795 genes were differentially expressed in chicken embryo fibroblasts infected with GX0101 with a reticuloendotheliosis virus LTR insert as compared to GX0101-ALV- LTR significantly. The differentially expressed genes were mostly associated with the regulation of transcription and the development of multiple organs. Based on the bio functions of the differential genes, infection of GX0101 was predicated with a greater development disorder of multiple systems, resulting in higher growth retardation, mortality, tumorigenicity, and immunosuppression in chickens than GX0101-ALV- LTR . Collectively, our results provided valuable insights into elucidation of the possible relationship between retro-viral LTR insert and the observed phenotypes caused by MDV recombinant viruses.